Globalizzazione e aspetti culturali: l’esempio del tatuaggio - Paolo Macchia (Bollettino della Società Geografica Italiana, 2020)
The ancient practice of skin drawing and tattooing is among the oldest and most recurrent cultural phenomena in the history of peoples and human societies around the world. Since prehistoric times cultures and civilizations have used it as a means of communication to convey personal information such as social position and relations, devotion, sense of belonging and rebellion. Consequently, tattooing has undergone progressive “resemantization” to meet the cultural needs of human groups.